2007
DOI: 10.1002/dneu.20377
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of dopaminergic neural network and locomotion function in planarian regenerates

Abstract: Planarian, an invertebrate flatworm, has a high capacity for regeneration when compared with other worms and animals. We show here for the first time that the reconstructed dopamine (DA) neural network regulates locomotion and behavior in planarian regenerates. The gene encoding tyrosine hydroxylase in the planarian Dugesia japonica (DjTH) was identified. DjTH protein was coexpressed with aromatic amino acid decarboxylase-like A (DjAADCA) in the planarian central nervous system (CNS). In addition, DjTH-knockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
130
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 131 publications
(135 citation statements)
references
References 35 publications
3
130
1
1
Order By: Relevance
“…Also, we found that a planarian netrin homologue (Djnetrin) is expressed in the junctions between visual neurons and the brain as well as between the VNCs and the brain (Cebrià et al 2002c;Cebrià & Newmark 2005). These analyses suggested that a variety of external signals received by these sensory neurons may be integrated in the DjotxBexpressing domain, where dopaminergic neurons are concentrated (Nishimura et al 2007), and that these integrated signals may be transferred to the body muscles through the VNCs (Tazaki et al 1999). Also, additional functional domains in the planarian brain have been defined by gene expression analyses, and give us a more complex view of this organ than suggested by its relatively simple morphology (Cebrià et al 2002a).…”
Section: Structure Of the Planarian Brainmentioning
confidence: 75%
“…Also, we found that a planarian netrin homologue (Djnetrin) is expressed in the junctions between visual neurons and the brain as well as between the VNCs and the brain (Cebrià et al 2002c;Cebrià & Newmark 2005). These analyses suggested that a variety of external signals received by these sensory neurons may be integrated in the DjotxBexpressing domain, where dopaminergic neurons are concentrated (Nishimura et al 2007), and that these integrated signals may be transferred to the body muscles through the VNCs (Tazaki et al 1999). Also, additional functional domains in the planarian brain have been defined by gene expression analyses, and give us a more complex view of this organ than suggested by its relatively simple morphology (Cebrià et al 2002a).…”
Section: Structure Of the Planarian Brainmentioning
confidence: 75%
“…anti-DjAADCA antibody (15) revealed that Djptc(RNAi) regenerants showed posterior fate in the anterior region, as indicated by their bifurcated branching (Fig. 1L).…”
Section: Resultsmentioning
confidence: 97%
“…38. After whole-mount in situ hybridization, specimens were subjected to immunohistochemistry using anti-DjAADCA or anti-DjSyt antibody essentially as described (15,32). In brief, specimens were incubated with the primary antibody (1:1,000 dilution) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…We recently discovered that the planarian CNS contains dopamine, serotonin, γ-aminobutyric acid (GABA) and acetylcholine, which are known to be present in mammalians, and that the planarian nervous system constitutes particular neural networks and functions [15][16][17][18][19]. Since planarians possess pluripotent stem cells throughout their entire bodies, their CNS can be completely regenerated along with recovery of morphology and function after amputation [20].…”
Section: Da Neuronal Regeneration In Regenerative Animalsmentioning
confidence: 99%
“…One involves DA neuroregeneration accompanied by brain regeneration after artificial amputation [15,21]. The other involves DA neuronal regeneration after selective degeneration of DA neurons by the DA neurotoxin 6-hydroxydopamine (6-OHDA) [22].…”
Section: Da Neuronal Regeneration In Regenerative Animalsmentioning
confidence: 99%